Role of magnesium in chronic kidney disease complications - Long Meng-tuan; Zhu Xiao-yu; Wei Xue-jiao; Zhao Dan; Jiang Li-li; Du Yu-jun (Linchuang shenzangbing zazhi)
Chronic kidney disease（CKD） is characterized by a high incidence rate and a high mortality.And irreversible pathological damage of CKD may progress to chronic renal failure and end-stage kidney disease.Untimely treatment has brought great harms to physical and mental health and economic burdens to patients.And CKD leads also to multiple systemic diseases, such as mineral bone disease, cardiovascular complications, neuropathies, muscular disorders, gastrointestinal dysfunctions and anemia.And these diseases will accelerate the progression of CKD.As a cofactor of many enzymes, magnesium may regulate energy and mineral metabolism, promote protein synthesis and antagonize inflammatory responses and antioxidant stress.Also it is capable of delaying the course of CKD,regulating multiple systemic diseases and improving patient prognosis.Kidney is also a vital regulatory organ of magnesium.Understanding the interactions between magnesium and CKD and its complications may provide theoretical rationales for using magnesium in CKD.